2007
DOI: 10.1007/s10265-007-0094-z
|View full text |Cite
|
Sign up to set email alerts
|

Salt impact on photosynthesis and leaf ultrastructure of Aeluropus littoralis

Abstract: The effects of salinity (400 mM NaCl) on growth, biomass partitioning, photosynthesis, and leaf ultrastructure were studied in hydroponically grown plants of Aeluropus littoralis (Willd) Parl. NaCl produced a significant inhibition of the main growth parameters and a reduction in leaf gas exchange (e.g. decreased rates of photosynthesis and stomatal conductance). However, NaCl salinity affected neither the composition of photosynthesis pigments nor leaf water content. The reduction in leaf gas exchange seemed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
60
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 58 publications
7
60
0
Order By: Relevance
“…The bundle sheath showed tightly packed cells around the vascular sheath. An adaptive role has been suggested for the bundle sheath under water stress because it stores water to buffer transpiration surges (Barhoumi et al, 2007). As suggested for Aeluropus littoralis, a halophytic salt excreter grown at similar salt levels to amylacea in this study, the osmotic stress induced by salinity has no significant effect on the volume or shape of maize BSC.…”
Section: Salt Effectsmentioning
confidence: 43%
See 1 more Smart Citation
“…The bundle sheath showed tightly packed cells around the vascular sheath. An adaptive role has been suggested for the bundle sheath under water stress because it stores water to buffer transpiration surges (Barhoumi et al, 2007). As suggested for Aeluropus littoralis, a halophytic salt excreter grown at similar salt levels to amylacea in this study, the osmotic stress induced by salinity has no significant effect on the volume or shape of maize BSC.…”
Section: Salt Effectsmentioning
confidence: 43%
“…Starch grains are typically restricted to BSC chloroplasts in C 4 plants (Leegood, 1985). It has been reported that starch accumulation is a generalized effect in salt-stressed plants (Barhoumi et al, 2007). In amylacea maize plants under high salt conditions, some BSC showed a starch grain accumulation ( Figures 2D and 2E).…”
Section: Salt Effectsmentioning
confidence: 79%
“…Thus, reduction in chlorophyll content and in the maximum potential quantum efficiency of PSII, measured as changes in chlorophyll fluorescence (F v /F m ) is related to the salinity-induced swelling and distortion of thylakoids, grana stacking, stroma and chloroplast envelope (Barhoumi et al 2007;Rahman et al 2000;Wang et al 2009;Yamane et al 2003Yamane et al , 2008. Therefore, these parameters are referred as efficient indicators for the evaluation of stress related effects on photosystem II (PSII) (Baker 2008;Netondo et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, the photosynthetic capacity of plants is unlimited when the optimal growing conditions are met. Unfortunately, terrestrial plants are constantly challenged by abiotic (UV, water, salinity, temperature) (Baker et al, 1988, Baldry et al, 1966, Barhoumi et al, 2007, Barrow and Cockburn, 1982, Bassham, 1977, Batista-Santos et al, 2011, Bauerle et al, 2007, Berry, 1975, Bischof et al, 2000, Ripley et al, 2008, Ripley et al, 2007, Roberntz and Stockfors, 1998 and biotic (pathogens, pests, animal and human) stresses that reduce their productivity and even threaten their survival (Bilgin et al, 2010, Bonfig et al, 2006, Erickson and Hawkins, 1980, Garavaglia et al, 2010, Kocal et al, 2008. While the regulation of plant defence responses has been extensively investigated, the effects of pathogen infection on primary metabolism, including photosynthesis, are however less known.…”
Section: Introductionmentioning
confidence: 99%